Pendampingan Penerapan Metode Tilawati Pada Pembelajaran Membaca Al-Qur’an Di Desa Jangraga - Muhamad Asim; Ali Mufti; Rianti Rianti; Irpan Ilmi; Dasep Supriatna; Laelatul Munawaroh; Ani Suryani; Nurhalimah Nurhalimah; Faiz Abdul Malik; Kamal Firmansyah; Etin Maryatin (Fakultas Teknik Universitas Cenderawasih, 2023)
The Tilawati method is a technique in learning the Qur’an that uses elements such as rhythm in reading the holy verses of the Qur’an. The Tilawati method is a way of learning to read the Al-Qur’an with the characteristic of using Rost songs with a balanced approach. This method can be taught verbally by combining rhythm and intonation to provide an interesting reading atmosphere while making students able to remember the verse better. The service method used is participatory action research by means of observation, outreach as well as providing assistance and evaluation. The result of this service activity is that teachers and students feel enthusiastic and happy when learning using the Tilawati method. The village residents really hope that the outcome of this activity will be that their children will be fluent and better at reciting the Qur’an and studying the Qur’an.